Strategi Pengembangan Sentra Batik Plalangan menuju Desa Wisata - Lutfi Hendriyati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2019)
The tourism village is a rural area that has some special characteristics that are worthy of being a tourist destination. The purpose of this study is to explain and describe the potential of the Plalangan Batik Center in preparing itself for the Tourism village, the strengths and weaknesses of the plalangan village to become a tourist village, and the Plalangan Batik Center Strategy, Sleman Yogyakarta to be developed into one of the tourist village attractions in Yogyakarta. The conclusion of this study is that the people in the village of Plalangan try to improve their ability and quality in realizing the Plalangan batik centre as a tourist village especially the quality of Human Resources. Large community support is one of the main capital in realizing rural tourism